المحددات الاقتصادية والاجتماعية للبطالة في السودان -دراسة قياسية باستخدام انحدار المركبات الرئيسة للمدة (1981-2015م) - عبد القادر, قريب الله عبد المجيد (Journal of Economics and Administrative Sciences, 2017)
Considering the magnitude of its economic, social and political impact, unemployment represents a crucial challenge confronting the majority of the countries of the world. The problem of the study was the high rates of unemployment in Sudan and the inability of economic growth rates to keep pace with the steady increases in unemployment rates during the study period. This study aimed to identify the economic and social variables influencing unemployment rate in Sudan, in addition to measuring the impact of these variables over the period (1981-2015). Data were collected from databases of the World Bank and Atlas of the World's data .The study hypothesized the presence of statistically significant and direct relationship between unemployment, and each of population and the dummy variable, which reflects the impact of the civil war on unemployment rates. The study also assumed the presence of inverse relationship between unemployment on the one hand, and Gross Domestic Product, Government Expenditure, Inflation Rate, and Gross Capital Formation on the other.   Econometric model was designed to measure the relationship between unemployment and its determinants. To avoid the expected collinearity problem among the independent variables, Principal Components Regression was employed to estimate the coefficients of the Model.. The study findings revealed to be congruent with economic theory, namely the presence of inverse statistically significant relationship between unemployment on the one hand and government expenditure, inflation rate, and gross capital formation on the other. Results also revealed the presence of direct statistically significant relationship between unemployment and the dummy variable, which entails the impact of civil war on unemployment rate.  Nonetheless, other findings revealed to be in contradiction with the economic theory, namely the direct relationship between unemployment and Gross Domestic Product as well as the inverse relationship between unemployment and population. The paper recommends re-evaluating higher education policies, so as to align learning outcomes with labor market needs to reduce unemployment rate. The study also recommends securing an attractive and stable environment to attract foreign investments, and launch promising projects capable of generating real job opportunities